Do COVID-19 related primary emotions affect risk perceptions, efficacy beliefs, and information seeking and behavior? Examining emotions as audience segments - Turner, Monique M.; Lim, Jong In; Jang, Youjin; Heo, Ruth Jin-Hee; Ye, Qijia; Kim, Miyeon; Lapinski, Maria Knight; Peng, Tai-Quan (Frontiers in Communication, 2024)
Primary emotions among populace about global health crisis such as the COVID-19 pandemic are informative. Guided by appraisal theories of emotions, this study explored emotional segmentations by mapping the primary emotions about the COVID-19 and investigating the impact of the emotions on cognitive and behavioral outcomes including risk perceptions, efficacy beliefs, behavioral intentions, prevention behaviors, and information seeking/avoidance. Study 1 investigated emotions about the COVID-19 among young adults (N = 1,368) and examined the effect of emotions on risk perceptions, efficacy beliefs, and behavioral intentions to practice mask wearing and physical distancing varied depending on their primary emotions.Study 2 replicated Study 1 and further tested the effect of primary emotions on preventive behaviors and information seeking/avoidance with a quota-based national sample of U.S. adults (N = 8,454). Results showed that most people experience negative emotions, such as sadness, anger, and anxiety, and showed various level of risk perceptions, efficacy beliefs, behavioral intentions and actual behavior, as well as information seeking/avoidance depending on what emotion one felt. Importantly, across both studies, anxious individuals showed more favorable health related perceptions and behavioral outcomes than angry ones reported. These findings provide insight into the emotional experiences of individuals during the COVID-19 pandemic and their impact on risk perceptions and health-related behaviors.